Chemical process engineering. Design, analysis, simulation, integration, and problem solving with Microsoft Excel-UniSim software for chemical engineers computation, physical property, fluid flow, equipment and instrument sizing / Volume 1, (2022) - Sotudeh-Gharebagh, Rahmat, 1964-; Coker, A. Kayode
No abstract available